2018
DOI: 10.1016/j.tranpol.2017.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Public transport policy measures for improving elderly mobility

Abstract: Population aging is happening in most of the world's metropolitan cities, and the proportion of elderly adults is predicted to increase significantly in the coming decades. This rapid growth of elderly populations may lead to serious transport issues when their mobility is compromised by the unavailability of public transport services. Public transport concession fare schemes are commonly implemented in many cities to encourage the elderly's participation in social activities. However, these policies emphasize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(88 citation statements)
references
References 35 publications
3
82
0
3
Order By: Relevance
“…The results from this research were accordingly also considered when devising the policy incentives included in the study presented in this paper. Wong et al (2018) examined the issue of population aging in metropolitan areas such as Hong Kong, and the role that policy can play in considering the interests of elderly mobility. A stated preference survey was conducted to investigate travel decision making of the elderly, which was analysed by means of a binary logistic regression model.…”
Section: Policy Incentives To Encourage Public Transport Usementioning
confidence: 99%
See 2 more Smart Citations
“…The results from this research were accordingly also considered when devising the policy incentives included in the study presented in this paper. Wong et al (2018) examined the issue of population aging in metropolitan areas such as Hong Kong, and the role that policy can play in considering the interests of elderly mobility. A stated preference survey was conducted to investigate travel decision making of the elderly, which was analysed by means of a binary logistic regression model.…”
Section: Policy Incentives To Encourage Public Transport Usementioning
confidence: 99%
“…This model identified the explanatory variables that influence trip making behaviour of elderly people for social trip purposes. The attributes considered in the experiment were travel fares, walking and wait times and seat availability, of which the results produced from the model showed that a higher travel fare and longer wait and walk times negatively influenced the elderly's willingness to travel (Wong et al, 2018), while the availability of seats had a positive effect on the likelihood of making a trip. Other noteworthy findings from this study were that seat availability and trip cost were found to be of higher statistical significance to the elderly travelling by bus rather than by rail, which supported the extension of a bus fare concession in Hong Kong.…”
Section: Policy Incentives To Encourage Public Transport Usementioning
confidence: 99%
See 1 more Smart Citation
“…There are two possible explanations. Firstly, different age cohorts have differing needs and preferences of services, for example health care services (Wong et al, 2018). Normally, young adults seldom go to hospital, so they may not consider proximity to hospitals when making residential location decisions, even tend to live far away from hospitals.…”
Section: Initial Hedonic Price Regressionmentioning
confidence: 99%
“…Binary logistic regression has been commonly used to forecast the probability of choice decisions from two alternatives for individuals based on utility maximization in the context of transport behavioral studies [56][57][58][59]. In this study, a binary model was applied to identify and investigate the major determinants of the choice between private car and public transport during shopping trips in Shenyang.…”
Section: The Regression Analysis Of the Studymentioning
confidence: 99%